Sialorrhoea Management Practices in Residential Older Adults Care Settings: A Qualitative Study. (30th December 2020) - Varley, Li Ping; Gooney, Martina; Denieffe, Suzanne; Murphy, Annette
Abstract: Aim: The aim of this research was to explore both older adults' and health care professionals' experience and views of sialorrhoea management practices in older adult residential care settings. Background: Sialorrhoea is quite a bothersome symptom among patients with certain neurological conditions. The complexity of sialorrhoea and its complications can be quite challenging for health care professionals. In the management of sialorrhoea, a multidisciplinary approach is proposed as an effective way of sialorrhoea management. Methods: Thematic analysis of collected data via semi‐structured qualitative interviews with five focus groups involving 28 multidisciplinary health care members and 1 patient. Results: The older adult and multidisciplinary health care professionals' view of the management of sialorrhoea in residential care settings were established under three main themes: 1) 'Sialorrhoea compromising patient's dignity', 2) 'Ad hoc local management' and 3) 'Further integration of care required'. Conclusion: At present, there have been no comprehensive multidisciplinary sialorrhoea management strategies to meet the various needs of older adults with sialorrhoea. Implication for Nursing Management: It is important to minimize the negative impact of sialorrhoea on the patients. The recognition of issues associated with sialorrhoea provides constructive scope for the health care professionals to further investigate and develop more effective integrated sialorrhoea care protocols.